Sustainable transformation agenda for enhanced global food and nutrition security: a narrative review - Oluwole, Oluwatoyin; Ibidapo, Olubunmi; Arowosola, Temiloluwa; Raji, Fatima; Zandonadi, Renata Puppin; Alasqah, Ibrahim; Lho, Linda Heejung; Han, Heesup; Raposo, António (Frontiers in Nutrition, 2023)
The world's population is currently growing at an exponential rate, which is estimated to be over 8 billion inhabitants as reported by United Nations on November 15, 2022. According to FAO, 870 million people out of this population do not have enough food to eat, with the vast majority of hungry people (98 %) living in developing countries, where almost 15% of the population is undernourished. Furthermore, the world's population is estimated to come to 9 billion by 2050, which would incur severe food scarcity and would seriously hamper global food security. Food losses, especially post-harvest loss as a result of poor agricultural practices have also been reported to greatly impact the economy, the environment, and the livelihoods of low and medium countries and Sub-Saharan-African. Therefore, realistic options should be established for promoting sustainable agriculture systems, improving nutrition, and achieving food security to end hunger in our nations. This paper elucidates the drivers of food insecurity including food losses, escalating population growth, hunger, and food production, among others, and provided some transformation approaches such as value addition through appropriate and emerging food processing and preservation techniques, application of biotechnological options through genetically modified foods and functional foods consumption and integration of indigenous underutilized nutrient-dense food crops which could serve as all-inclusive and sustainable transformation options for enhanced food and nutrition security, especially in developing countries, which is where the hunger burden and the prevalence of malnutrition and non-communicable diseases are high.